Transformation of Student Cheating in Web 2.0 - Katerina Zdravkova (UPMC, 2014)
Many students don’t choose the rightful means to pass their exams. Their main goal is to successfully finish the assignments with a minimum possible effort. New technologies that implement social media and interactive collaboration have triggered the remodelling of frauds and tricks students implement. Such remodelled cheating activities are more concealed, thus more difficult to discover. This paper presents the most common traditional student frauds contrasted with the transformed techniques emerged from the introduction of e-Learning 2.0. The measures applied to detect the existence of various kinds of cheating and recommendations how to reduce them are introduced together with the limits set by interactive techniques and teacher’s activities to prove the suspected scam. The estimation of the frequency of the different types of cheating is presented in parallel with the results of an anonymous questionnaire revealing student impression about fraudulent behaviour of their colleagues and themselves. The paper proves that without a proactive implementation of protection measures to prevent cheating, many students will resort to different kinds of dishonesty in order to accomplish their ultimate goal to pass the exam with no remorse.
Keywords: Ghostwriting; External and internal plagiarism; Identity swap; Sharing using messages or private files; Vandalizing of wikis